Managing supplier relationships in a new product development context. Issue 3 (September 2015) - Sjoerdsma, Maarten; van Weele, Arjan J.
Abstract Organizations can no longer rely solely on their own resources to innovate and therefore look for strategic interactions outside their organizational boundaries. During the past years Early Supplier Involvement, supplier relationship management (SRM) and knowledge exchange in supply chain relationships have been separately covered in academic research. Using insights from RBV Theory this study proposes and validates an integrated framework that explains outcome effects of new product development (NPD) projects. The initial framework was derived from existing research and validated using four in depth case studies studying actual global NPD projects taken from a large multinational company. The case study findings resulted in a revised framework that can be used to assess NPD outcomes of buyer–supplier interactions. Our research confirms that a positive relationship between relationship quality, knowledge transfer and NPD outcomes exists. Twelve constructs appear decisive for buyer–supplier relationship quality. These constructs act on either an individual or organizational level. A better relationship quality allows for more knowledge transfer among partners, more (innovative) ideas and solutions and positive NPD project outcomes. The reverse, however, also appears to be the case. The proposed integrated framework can be used to predict the performance of a NPD project by measuring the quality of the relationship between buyer and supplier on the twelve constructs. As such this research advances our understanding of the importance and dynamics of supplier relationship management in NPD projects. Future research, however, is needed to further validate and test the proposed framework.